The current state of public health education in India: A scoping review - Joshi, Ashish; Bhatt, Ashruti; Gupta, Mansi; Grover, Ashoo; Saggu, Sofia Rani; Malik, Isha Vikas (Frontiers in Public Health, 2022)
With the creation of public health management cadre in the state, district, and block levels of India, there is a need for a comprehensive, synergistic education system to ensure efficient public health across the country. This scoping review, therefore, aims to examine the characteristics of public health education programs available in India's varied geographical and regional contexts. It examines sixteen program-related descriptors across public health Doctoral, Masters, Bachelors, Post-graduate Diploma, and Diploma education programs offered. Information Data was retrieved through institutional websites. Results of our analysis showed 84 unique institutions in 20 states and 3 UTs currently offering 116 public health programs across India's 28 states and 8 UTs. Private and public institutes were 65% (n=75) and 35% (n=41) respectfully. The majority of universities mainly provided Masters of Public Health (n=73, 63%) programs followed by Postgraduate Diploma (PGD) and Diploma (n=17, 15%), BPHSc (n=14, 12%), and Ph.D. (n=12, 10%). The majority of Ph.D. programs in public health are offered in Maharashtra, Karnataka, and Haryana, while Masters in Public Health programs are offered highest in Karnataka, Bachelors in Public Health programs in Rajasthan, Post Graduate Diploma in Public Health program in Delhi, and Tamil Nadu had the most number of Diploma in Public Health programs. Thirty-one percent (n=36) of the public health programs are offered across the south, 28% (n=32) across the north, and 22% (n=26) across the west Analyzed descriptors provide comprehensive information on program characteristics, mainly admission, format, and tuition fee. The review offers five suggestions to improve collaborative public health education and prepare a workforce with the skills, knowledge, and expertise to respond to the 21st century's public health threats and challenges in India.